Jamaah Keagamaan Melawan Covid-19: Studi Pada Tempat-Tempat Ibadah Di Kota Kendari - Jalil, Abdul; Ashmarita, Ashmarita (POROS ONIM: Jurnal Sosial Keagamaan, 2022)
This study aims to reveal congregational activities during the implementation of restrictions on community activities from August to October 2021. There is an impression that the stricter the regulation of activities in places of worship, the stronger the community's desire to perform worship in their worship places, including other social religious activities. This study uses a qualitative descriptive method through an ethnographic approach. Observations were made in several places of worship. Informants were chosen deliberately, namely people who are considered to understand the problem under study. The theory used is Bourdie's power which explains that any social phenomena including religious congregations in carrying out their activities are individual actions. They still hold worship, even though they have been given an appeal in the form of strict regulations. The results of the study show that congregations are already aware of the dangers of Covid-19, but at the same time they cannot be separated from activities in places of worship because it is a habit since childhood and has been passed down from generation to generation. In the context of fighting Covid-19, religious leaders agree more with the term peace with Covid-19. This means continuing to worship in places of worship, but being aware of strict health protocols is the main key for every individual.